Aristotelian Priority, Metaphysical Definitions of God and Hegel on Pure Thought as Absolute. Issue 1 (April 2020) - Kreines, James
Abstract: This paper advances a philosophical interpretation of Hegel's Logic as defending a metaphysics, which includes an absolute, itself comparable to God in other systems of metaphysics of interest to Hegel, including Aristotle's and Spinoza's. Two problems are raised which can seem to block the prospects for such a metaphysically inflationary interpretation. The key to resolving these problems is consideration of the kinds of metaphysical priority that Hegel sees in Aristotle. This allows us to build a philosophical model of Hegel's absolute, and to demonstrate how the model fits the argument of Hegel's Logic . Application of this model provides a philosophical explanation of the senses in which Hegel's metaphysics is idealist; he argues that thought is absolute and comparable to God in other systems of metaphysics: thought is both self-determining and metaphysically prior to being.